The Impact of Citizens' Perceptions on Professionalism, Work Communication, and Motivation on Employee Performance in Citangtu Village - Adry Setia Abdul Majid; Muhamad Alwi (International Journal of Business, Economics, and Social Development, 2026)
Public services at the village level require professional, communicative, and highly motivated civil servants who directly interact with the community. Residents’ perceptions of the quality of civil servants play a crucial role in reflecting and influencing employee performance. This study analyzes the impact of residents' perceptions of professionalism, work environment communication, and work motivation on the performance of employees in Citangtu Village, Kuningan District. A quantitative approach with an explanatory method was employed. Data were collected using a Likert scale questionnaire from 100 residents of Citangtu Village who had received public services. Data analysis was performed using SPSS, involving validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. Hypothesis testing was conducted using t-tests, F-tests, and the coefficient of determination (R²). Results showed that professionalism, communication in the work environment, and work motivation had a significant impact on employee performance. However, professionalism alone did not significantly affect performance, while communication and work motivation showed a positive and significant effect. Communication emerged as the most dominant factor influencing employee performance. The high coefficient of determination suggests that most of the variation in employee performance can be explained by these three independent variables. These findings indicate that improving employee performance requires more than professionalism; strengthening communication and enhancing motivation are equally essential.